Medallion-like dermal dendrocytoma - Melissa Alexander; Lubna Rizwan; Adelle T Quintana; Viktoryia Kazlouskaya; Dirk Elston (Wolters Kluwer Medknow Publications, 2014)
Medallion-like dermal dendrocytoma is a benign cutaneous neoplasm that mimics dermatofibrosarcoma protuberans histologically. The distinction between these two entities is critical to prevent unnecessary wide excisions. Herein we describe an acquired MLDD in a 55-year-old female.